2021
DOI: 10.1039/d0sm02261f
|View full text |Cite
|
Sign up to set email alerts
|

Keratins determine network stress responsiveness in reconstituted actin–keratin filament systems

Abstract: The cytoskeleton is a major determinant of cell mechanics, and alterations in the central mechanical aspects of cells are observed during many pathological situations. Therefore, it is essential to investigate...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 63 publications
4
51
0
Order By: Relevance
“…This agrees with the observed increase in stickiness since the rubber behavior is caused by the transition from an entangled to a crosslinked network. [ 28–30 ] Our findings also illustrate that the increased resistance is not simply caused by the inherently higher solvent viscosity of D 2 O compared to H 2 O [ 10,11 ] since this would not result in a more pronounced rubber‐like behavior. In fact, viscous contributions of the in vitro systems are hardly affected by different H 2 O/D 2 O ratios (see Figure S3, Supporting Information).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This agrees with the observed increase in stickiness since the rubber behavior is caused by the transition from an entangled to a crosslinked network. [ 28–30 ] Our findings also illustrate that the increased resistance is not simply caused by the inherently higher solvent viscosity of D 2 O compared to H 2 O [ 10,11 ] since this would not result in a more pronounced rubber‐like behavior. In fact, viscous contributions of the in vitro systems are hardly affected by different H 2 O/D 2 O ratios (see Figure S3, Supporting Information).…”
Section: Discussionmentioning
confidence: 66%
“…In this respect, it is known that deuterium bonds of D 2 O are slightly stronger than the hydrogen bonds of H 2 O [10] and that D 2 O may enhance hydrophobic interactions. [26] Within the glassy worm-like chain model, [27][28][29][30] these interactions are modeled as a stickiness parameter (ε), and a higher ε reflects stronger inter-filament interactions. We found that the stickiness parameter increases under D 2 O conditions non-monotonically from ε = 1.8 for normal H 2 O conditions to 4.6 and 2.7 for the respective D 2 O concentrations (see Supporting Information; since multiple factors can impact the viscoelastic behavior of actin networks, we speculate that the non-monotonic behavior of ε could be caused by a D 2 O induced shortening of filaments).…”
Section: Resultsmentioning
confidence: 99%
“…With keratins, the impact of actin is different. Actin causes a steric hindrance, which reduces the bundling of keratin IFs [111,112]. Bulk shear rheology shows that, at low strain, the viscoelastic behavior of actin and K8/18 composite networks reconstituted in vitro is intermediate between that of pure networks.…”
Section: Intermediate Filaments Affect the Mechanics Of Cytoskeletal Composite Networkmentioning
confidence: 99%
“…Bulk shear rheology shows that, at low strain, the viscoelastic behavior of actin and K8/18 composite networks reconstituted in vitro is intermediate between that of pure networks. When submitted to large deformations, the addition of K8/18 increases the strain-stiffening properties and the yield stress [112]. Compared to vimentin, keratin is more efficient in increasing composite network strainstiffening [110,112].…”
Section: Intermediate Filaments Affect the Mechanics Of Cytoskeletal Composite Networkmentioning
confidence: 99%
See 1 more Smart Citation